Two new cembranoids from the leaves of Croton longissimus Airy Shaw - Kawakami S. (2014)
Two new cembrane-type diterpenoids (1 and 2) along with five known compounds (3-7) were isolated from leaves of Croton longissimus collected in Thailand. Their structures were elucidated from spectroscopic evidence and compound 4 was found by HPLC analysis to be identical to oblongionoside B - a compound isolated from Croton oblongifolius - including the absolute configuration at the C-9 position. © 2012 The Japanese Society of Pharmacognosy and Springer.